2011
DOI: 10.1093/deafed/enr049
|View full text |Cite
|
Sign up to set email alerts
|

Social Competence, Sense of Loneliness, and Speech Intelligibility of Young Children With Hearing Loss in Individual Inclusion and Group Inclusion

Abstract: The study focused on social competence (SC) and perceived sense of loneliness of preschool children with hearing loss (HL) in group inclusion (GI, a small group of children with HL is integrated in a standard classroom) and individual inclusion (II, each child with HL is individually integrated into a standard classroom). The relations between these factors and the child's speech intelligibility were performed. Sixty-four children aged 4-7 years participated: 22 from an II and 42 from a GI. SC, perceived sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…The communication barrier between HI and NH children can function as an obstacle for successful interpersonal relationships and may hamper these children in developing solid social networks [51], [52]. This process may pave the way for social isolation and loneliness, with consequences for the child's self-esteem [53], [54]. Hence, by improving language development and communication skills, the HI child might experience better contact with peers, which in turn would likely improve their self-esteem in this domain.…”
Section: Discussionmentioning
confidence: 99%
“…The communication barrier between HI and NH children can function as an obstacle for successful interpersonal relationships and may hamper these children in developing solid social networks [51], [52]. This process may pave the way for social isolation and loneliness, with consequences for the child's self-esteem [53], [54]. Hence, by improving language development and communication skills, the HI child might experience better contact with peers, which in turn would likely improve their self-esteem in this domain.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that social maturity was measured via self-report in this study, however, and Antia, Jones, Luckner, Kreimeyer, and Reed (2011) found that deaf children appeared overly confident in self-reports of social competence relative to parent and teacher ratings. Furthermore, deaf individuals with poor social competence, or simply poor communication skills, may be less aware of subtleties in social interactions and the extent of their delays (Most, Ingber, & Heled-Ariam, 2012;Punch & Hyde, 2011).…”
Section: Relations Among Communication Social Maturity and Executivmentioning
confidence: 99%
“…Mainstreamed deaf children have much more limited interactions with their hearing peers than the hearing children do with each other (KEATING;MIRUS, 2000). Indeed, studies reveal the loneliness that deaf children feel (NUNES;PRETZLIK;OLSSON, 2001;ELHAGEEN, 2004;MOST, 2007;MOST;INGBER;HELED-ARIAM, 2011). When deaf adults look back on their childhood, they remember suffering from loneliness (LEVINGER;ORLEV, 2008), and Kurz, Hauser, and Listman (2016, p. 88) Activities that cause spontaneous laughter are exactly what the deaf child needs in order to feel truly included in school and to make friends.…”
Section: Humor and Inclusionmentioning
confidence: 99%
“…If she is so inclined, she can avail herself of the richness that YouTube offers in the way of presenting Deaf Culture, encouraging students to mimic stories, such as those of the Teatro Alegria Surda (PINHEIRO, 2011) and RISE (MIRUS; NAPOLI, 2018). Silveira and colleagues(2011) suggest that she bring to the inclusive classroom stories in Deaf Culture that focus on joy, love, and optimism, with illustrations of smiling characters. Such stories help develop deaf identity(SUTTON-SPENCE, 2010) and can help all children who are dealing with dilemmas, uncertainty, and ambiguity, as some deaf children are (for a retrospective from deaf adults' point of view, seeKUSHALNAGAR et al, 2017).…”
mentioning
confidence: 99%